Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T20:51:16+01:00
(x-5)²=x²+15
x²+25-10x=x²+15
x²-x²-10x=15-25
-10x=-10 / :10
x=1


-(2a-5)²=(1-2a)(1+2a)
-4a²-25+20a=1-4a²
-4a²+20a+4a²=1+25
20a=26 / :20
a= 1,3


Pa=x²
Pb=(x-4)²
Pb=x²+16-8x

Pb-Pa = x²+16-8x -x²
= 16-8x
2010-03-12T20:52:04+01:00
1.
a)
(x-5)²=x²+15
x²+25-10x=x²+15
x²-x²-10x=15-25
-10x=-10 |:10
x=1
b)
-(2a-5)²=(1-2a)(1+2a)
-4a²-25+20a=1-4a²
-4a²+20a+4a²=1+25
20a=26 |:20
a= 1,3
2.
P1=x²
P2=(x-4)²
P2=x²+16-8x

P2-P1= x²+16-8x -x² = 16-8x
Odp. Pole drugiego kwadratu jest większe o 16-8x od pola pierwszego kwadratu.